Action research, innovation and change : international and interdisciplinary perspectives - Rauch, Franz; Stern,Thomas; Townsend, Andrew; Schuster, Angela (London : Routledge, 2014)
'Action Research is a discipline which continues to see a growth in interest both internationally and across disciplines. This book clearly demonstrates the growing diversity in settings and focus for action research and provides a clear guide to the core aspiration of all action research: to achieve principled change. Written by authors from a range of countries and range of disciplines, this book answers questions that are key to all researchers:How can action research be used to achieve principled change?How has action research been applied in different disciplines?How has action research been interpreted in different countries?What can be learnt about the conduct of action research from these diverse settings?Providing both detailed case studies of successful projects and discussions that challenge and raise theoretical questions about the conduct of action research this book explores some of the contemporary cutting edge applications and conceptualisations of action research. Action research paves the way for the empowerment of people involved in social action, and the examples of successful change processes that are the core of this book will prove inspirational and provide practical advice. Written by a range of leading international researchers in the field this book will define the future for Action Research for years to come.'--
Keywords: Action research -- Case studies